OPTIMIZATION OF THE IMPLEMENTATION OF EARLY INTERVENTION DETECTION STIMULATION FOR GROWTH AND DEVELOPMENT (SDIDTK) IN TODDLERS WITH THE DEVELOPMENTAL PRE-SCREENING QUESTIONNAIRE (KPSP) TOWARDS VILLAGE MIDWIVES - Katili, Rusli A; Irwan, irwan (International Journal of Health Science & Medical Research, 2024)
The Indonesian government has made maximum efforts to optimize toddler development and prevent deviations through the Early Growth and Development Stimulation, detection, and Intervention (SDIDTK) program. However, the implementation of SDIDTK still needs to be improved, and only 53% of the work area implements it. Health Center Estuary Enim. SDIDTK training intervention has never been conducted in the midwife village of Estuary Enim. The novelty of this research is that the researcher analyzed the optimization of the implementation of (SDIDTK) in toddlers, with Questionnaire Pre Screening Development (KPSP) Towards Village Midwives. The purpose of this study was to determine the optimization of the implementation of early intervention detection stimulation for growth and development (SDIDTK ) in toddlers with a questionnaire for pre-screening development (KPSP) on village midwives. The method used in the quasi-experimental research and the research design used one group pretest and posttest design. The sample in this study was 36 Village Midwives. The results of this study showed that the implementation of SDIDTK and KPSP was mostly carried out (69.4 % ), while the rest was not carried out (30.6%). The implementation of SDIDTK and KPSP before the study was 69.08 ± 9.90; then, knowledge increased after the study, namely 96.89 ± 4.05. An increase in knowledge was obtained by 27.80 ± 10.36. The conclusion is that there is an effect of optimizing the implementation of SDIDTK in toddlers with KPSP on village midwives